Hubungan Dukungan Keluarga Terhadap Kepatuhan Melakukan Kontrol Rutin Pada Penderita Diabetes Melitus di Klinik Pratama Balai Pengobatan Jatibening - Oktaviani Wulandari; Cusmarih Cusmarih (Universitas Malahayati Lampung, 2024)
ABSTRACT Diabetes Mellitus Is a condition when the body cannot use or produce sufficient amounts of insulin, then the body will experience diabetes mellitus, a complicated chronic condition that requires ongoing medical care to prevent complications and manage multifactorial risks beyond glycemic management. (American Diabetes Association, 2018). To determine whether there is a relationship between family support and routine control compliance in people with diabetes mellitus at the Jatibening Medical Center Primary Clinic in 2023. This research sample is all patients with diabetes mellitus at the Jatibening Medical Center Pratama Clinic in 2023. With Random sampling technique. The results of the chi square test show that there is a relationship between family support for compliance with routine control in people with diabetes mellitus at the Jatibening Primary Hall Primary Clinic in 2023 as many as 36 respondents and P value results of 0.039 (P0.05). There is a relationship between family support for compliance with routine control for people with diabetes mellitus at the primary clinic of the Jatibening Medical Center in 2023. Keywords: Routine Control Compliance, Family Support, People with Diabetes Mellitus. ABSTRAK Diabetes Melitus Merupakan kondisi ketika tubuh tidak dapat menggunakan atau memproduksi insulin dalam jumlah yang cukup, maka tubuh akan mengalami diabetes melitus, suatu kondisi kronis yang rumit yang memerlukan perawatan medis yang berkelanjutan untuk mencegah komplikasi dan mengelola risiko multifaktorial di luar manajemen glikemik. (American Diabetes Association, 2018). Untuk mengetahui apakah ada hubungan antara dukungan keluarga dengan kepatuhan kontrol rutin pada penderita diabetes melitus di Klinik Pratama Balai Pengobatan Jatibening Tahun 2023. Sampel penelitian ini seluruh pasien penderita diabetes melitus di Klinik Pratama Balai Pengobatan Jatibening Pada bulan Tahun 2023. Dengan Teknik Random sampling. Hasil uji chi square menunjukan bahwa adanya hubungan dukungan keluarga terhadap kepatuhan melakukan kontrol rutin pada penderita diabetes melitus di Klinik Pratama Balai Pengoatan Jatibening Tahun 2023 sebanyak 36 Responden dan hasil P value 0,039 (P0,05). Adanya hubungan dukungan keluarga terhadap kepatuhan melakukan kontrol rutin pada penderita diabetes melitus diklinik pratama balai pengobatan jatibening tahun 2023. Kata Kunci: Kepatuhan Kontrol Rutin, Dukungan Keluarga, Penderita Diabetes Melitus.